CONTRIBUTIONS TO THE INDIAN JOURNAL OF VETERINARY AND ANIMAL SCIENCES RESEARCH (IJVASR): A SCIENTOMETRIC ANALYSIS - L., Rajendran (International Journal of Research -GRANTHAALAYAH, 2021)
A Scientometric study was performed on 235 research articles published in the Indian Journal of Veterinary and Animal Sciences Research (IJVASR). For the current analysis, six volumes of the journal totalling 30 issues from 2016 to 2020 were considered. The amounts of contributions, authorship patterns, author productivity, average article length, and average keyword density have all been examined. Only 20 of the 235 contributions were single-authored, while the rest were multi-authored, with an average degree of collaboration of 0.91 and a week of collaboration between the writers. The increasing tendency of co-authored publications was highlighted by the pattern of co-authorship. According to the research, author productivity is 0.26.